(untitled) (Experimental biology, 2023)
The objective of this study was to identify the effect of the training process on the parameters of the immune system in wrestlers at various stages of training. It was established that in the preparatory and competitive periods of the training macrocycle, under the effect of physical loads in athletes, the total content of CD3+ -, CD4+ -, CD8+ - lymphocytes decreases in the peripheral blood with the formation of a relative hyper suppressive variant of the immunodeficiency state. There is no complete normalization of the parameters of the subpopulation composition of lymphocytes in the transition period. The inclusion of an additional transitional period in the training macrocycle contributes to a more complete recovery of the studied indicators. The use of restorative agents in the transitional period of the training process not only contributes to the optimization of several immune indicators of wrestlers, but also significantly reduces the impact of the seasonal factor on those wrestlers. The biggest effect of recovery measures happens in the spring, the optimization of the immune status of moderate severity took place in the winter and summer periods of the year. It should be mentioned that in the transition period of the training cycle of a significant reduction in intense physical and mental stress in wrestlers, the correction of the immune status with the help of a complex of rehabilitation measures was effective, regardless of the season with a maximum effect in the autumn.